(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the clusterization of regions of the Volyn region in 2014 was carried out on the basis of general coefficients of birth-rate and death rate, of coefficient of феминизации, of amount of marriages and of general coefficient of migratory increase. Аnalytical and graphical possibilities of application of programmatic package of STATISTICA 6.1 were shown for realization of multidimensional groupment at the analysis of demographic processes of separate region of country. Dendrogramof the regions of Volyn region in terms of reproduction of the population in 2014 was built. The main descriptive statistics for each formed cluster were described.